Child feeding in rural northern Ghana: Carer's perceptions of food and their children's diets. Issue 2 (1st October 2020) - Kukeba, Margaret Wekem; Fallon, Debbie; Callery, Peter
Abstract: A child's diet should be composed of appropriate nutrients to achieve optimal nutritional status, and though there is a substantial evidence base for child feeding recommendations, developing countries continue to face challenges regarding optimal child feeding. This paper describes an ethnographic study undertaken in rural northern Ghana to explore community perceptions of what 'counts' as food for children and the impact this had on the nutrients they received. Fifteen households with children under 5 years were purposively selected. In‐depth interviews were held with 25 mothers, 7 fathers and 8 grandparents within these households as well as 2 diviners. Participant observations were also undertaken. Findings show that satiety rather than nutrition was the key consideration in adult choices about a child's diet. The community regarded carbohydrate‐based meals as food, but considered protein, vitamins and mineral‐based foods as nonessential elements of a child's diet, and important sources of these nutrients were regarded as treats.